2022
DOI: 10.3389/fphys.2022.986881
|View full text |Cite
|
Sign up to set email alerts
|

Physical active lifestyle promotes static and dynamic balance performance in young and older adults

Abstract: Although regular physical activity exposure leads to positive postural balance control (PBC) adaptations, few studies investigated its effects, or the one of inactivity, on PBC in populations of different age groups. Thus, this study investigated the impact of a physically active lifestyle on static and dynamic PBC in young and older adults. Thirty-five young physically active subjects (YA), 20 young sedentary subjects (YS), 16 physically active older adults (OA), and 15 sedentary older adults (OS) underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Despite the limitations, the present study reinforces that postural control is influenced by the practice of physical exercise and active elderly women have a smaller COP displacement compared to inactive elderly women 9,38,39 . This reinforces the idea that the lower postural control and consequent higher risk of falls among inactive elderly women may not only be due to the aging process, but also to factors related to physical inactivity 18,40 .…”
Section: Resultssupporting
confidence: 84%
“…Despite the limitations, the present study reinforces that postural control is influenced by the practice of physical exercise and active elderly women have a smaller COP displacement compared to inactive elderly women 9,38,39 . This reinforces the idea that the lower postural control and consequent higher risk of falls among inactive elderly women may not only be due to the aging process, but also to factors related to physical inactivity 18,40 .…”
Section: Resultssupporting
confidence: 84%
“…In this study, COP data were only different in corrected vision and eyes-closed states, but there was no difference between COP data of myopia and those of other states. This may be because the participants recruited in this study were young male undergraduates, and the task of standing on two feet under different visual states was relatively simple and not challenging for them ( Sarto et al, 2022 ). In a study on the effect of corrected vision on postural stability, Bae et al (2020) found that the static postural stability of uncorrected visual acuity (without glasses) was significantly lower than that of the corrected state.…”
Section: Discussionmentioning
confidence: 99%
“…9 Resistance exercise preserves and increases muscle mass and strength while suppressing muscular atrophy by secreting myokines implicated in muscle cell proliferation, differentiation, and growth. 10 Furthermore, physical activity positively contributes to postural balance control by altering the effectiveness of sensory inputs and motor outputs, 11 resulting in improved dynamic and static balance and decreased fear of falling in older adults. 12,13 Older adult females are more likely than older adult males to experience physical weakness, falls, low selfesteem, fear of injury, and a lack of desire to be active.…”
mentioning
confidence: 99%
“…A literature review shows that the OEP is safe and effective in lowering the risk of falling or preventing falls in older adult Western and Asian populations. 11,12,17,18 However, there is insufficient evidence to support the effectiveness of the OEP as a fall prevention program in South Korea, where the geriatric population is growing at the fastest rate among the Organisation for Economic Co-operation and Development (OECD) countries. 19 In this study, we hypothesized that more frequent attendance of the OEP would result in greater fall risk prevention benefits for elderly Korean women through greater improvements in functional performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation